A Prospective Study Analyzing One‐Year Multidimensional Outcomes in Living Lung Transplant Donors. Issue 11 (18th September 2013) - Chen, F.; Oga, T.; Sakai, H.; Matsumoto, I.; Yamada, T.; Sato, M.; Aoyama, A.; Bando, T.; Mishima, M.; Chin, K.; Date, H.
Abstract : The success of living‐donor lobar lung transplantation (LDLLT) largely depends on donor outcome; but to date, no authors have studied health‐related quality of life (HRQOL) of donors. We prospectively evaluated multidimensional outcomes before and 1 year after donor lobectomies. Patient‐reported HRQOL, dyspnea, psychological status and sleep quality, and physiological pulmonary function were determined. All donors were alive without any limitations in their activities of daily living after 1 year. Postoperative pulmonary function was better than the estimated preoperative values; but, with respect to HRQOL, four of the eight subscales of the Medical Outcomes Study 36‐item short form (SF‐36) deteriorated significantly after donation. In addition, dyspnea assessed by the modified Medical Research Council scale also worsened significantly. In contrast, postoperative anxiety assessed by the Hospital Anxiety and Depression Scale significantly improved from baseline. The donors whose recipients died reported lower SF‐36 scores with worsening sleep quality measured by Pittsburgh Sleep Quality Index. Thus, although postoperative pulmonary functions in donors were preserved, their HRQOL and dyspnea deteriorated postoperatively. Moreover, HRQOL and sleep quality were impaired in recipients who experienced poor outcomes. To capture the comprehensive outcomes in LDLLT donors after donation, patient‐reported outcomes should be analyzed separately from physiological outcomes. Abstract : In a prospective evaluation of multidimensional outcomes in living lung transplant donors both before and after donation, the authors note possible postoperative deterioration in several aspects of health‐related quality of life and dyspnea, although postoperative pulmonary functions were preserved.